Proceedings of 4th ACM SIGCOMM Workshop on Network and System Support for Games 2005
DOI: 10.1145/1103599.1103624
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of factors affecting players' performance and perception in multiplayer games

Abstract: In this paper we analyse different factors affecting players' perception and performance in multiplayer games. We introduce a mean opinion score metric borrowed from the subjective analysis of audio and video content to classify the player's perceived game quality. With a survey we investigated the player's view on network latency for a variety of games. Furthermore, we examine four different games under different network conditions and collect data on game score and subjective perception from every player. Du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
87
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(91 citation statements)
references
References 7 publications
(15 reference statements)
4
87
0
Order By: Relevance
“…Similar results were presented by Dick et al in [9]. While experimenting with real-time network games, on a sample of 8 players, they showed that under the same network conditions (delay and delay variation) the quality of the game play experience varies between the players.…”
Section: Introductionsupporting
confidence: 82%
“…Similar results were presented by Dick et al in [9]. While experimenting with real-time network games, on a sample of 8 players, they showed that under the same network conditions (delay and delay variation) the quality of the game play experience varies between the players.…”
Section: Introductionsupporting
confidence: 82%
“…Dick et al analyzed how network latency and jitter affected the performance and perception in multiplayer online games (wired) [16]. This paper presents a survey where players state their subjective perceptions for how network latency and jitter affect the performance and gameplay for twelve different games representing four different game genres: first-person shooter, real-time strategy game, sport game, and car racing simulation.…”
Section: Games and Networkmentioning
confidence: 99%
“…Variations in packet size, buffer delay, and routing create packet jitter. The influence of the jitter in games is measured in [26], [31], [32], and [33]. They conclude that jitter had only a minor impact on the win probability, the scores and the user experience.…”
Section: Related Literaturementioning
confidence: 99%